Hubungan Pendidikan dan Manajemen Usaha Terhadap Pendapatan Petani Holtikultura - Melkis A.L. Oematan; Frans Gana; J.N. Kallau (Peneliti.net, 2020)
This research aims to identify relationship between education and business management towords horticulture farmers’ income of the collective business farmer group in Nobelki Vilage, Kupang. A quantitative approach was applied upon this research, were data collection was conducted through instrumen spread and documentation. Research results point a positive and significant relationship between education and business management towords horticulture farmers’ income where multiple linear regression’s rest was to be as Ftest 4.651 (0,5 significance), whilist Ftable was 2.802. Therefore Ftest>Ftable or 4.651>2.802. Further test point a significant effect of education towards horticulture farmers income. There is a significant effect of business management towards horticulture farmers income, whereas simple linear regression (Ttest) was to be as (-) 0.544 (.05 significan), whilst Ttable was -2.021. Therefore, Ttest>Ttable or (-0.544)>(-2.021). Determination test shows a relative contribution of education and business management towards holticulture farmers income, which was 16.2%. Partially, contribution by education was 11 % were as contribution by business management was 10%.